Municipal water planning and management with an end-use based simulation model. (March 2018) - Wang, Kai; Davies, Evan G.R.
Abstract: This study introduces an end-use-based system dynamics model to support municipal water planning and management over the medium-to long-term. The Calgary Water Management Model (CWMM) simulates water demand and use to 2040 at a weekly time step for ten municipal end-uses, as well as the effects of population growth, climate change, and various water management policies, and includes policy implementation costs for assessment of conservation versus economic trade-offs. The model was validated against historical water demand data for Calgary, Alberta. A series of scenario simulations showed (1) potentially large changes to both seasonal and non-seasonal water demands with climate change and population growth, (2) a need to enhance historical water management policies with new policies such as xeriscaping and greywater reuse to achieve water management goals, and (3) the value of an end-use based model in simulating management policy effects on municipal water demand and use. Highlights: Model simulates climate change, population growth, and water conservation programs. End-use based model structure simulates management policy effects. Weekly time step reveals both short- and long-term water demand and use patterns. Results reveal conservation policy costs and effects to improve management insight.